Effects of increasing amounts of supplemental soybean meal on intake and digestibility of tallgrass-prairie hay - C.P. Mathis; R.C. Cochran; J.S. Heldt; B.C. Woods; Gerald L. Stokka; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 1998)
Twenty ruminally fistulated beef steers free-choice access to prairie hay were used to evaluate the effect of increasing level of soybean meal (SBM) on forage intake and digestion. Forage intake, total organic matter intake, and organic matter digestion were enhanced with increasing level of SBM supplementation, although forage intake and digestion appeared to plateau at higher levels. The concomitant rises in intake and digestion as supplemental SBM increased resulted in an increase in total digestible organic matter intake, with the largest response to the initial increment of supplement.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Steers; Forage; Intake; Digestion; Soybean meal